2012
DOI: 10.1093/toxsci/kfs094
|View full text |Cite
|
Sign up to set email alerts
|

CYP450-Dependent Biotransformation of the Insecticide Fipronil into Fipronil Sulfone Can Mediate Fipronil-Induced Thyroid Disruption in Rats

Abstract: In rats, the widely used insecticide fipronil increases the clearance of thyroxine (T(4)). This effect is associated with a high plasma concentration of fipronil sulfone, the fipronil main metabolite in several species including rats and humans. In sheep, following fipronil treatment, fipronil sulfone plasma concentration and thyroid disruption are much lower than in rats. We postulated that fipronil biotransformation into fipronil sulfone by hepatic cytochromes P450 (CYP) could act as a potential thyroid disr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 37 publications
3
45
0
2
Order By: Relevance
“…Also our results confirm the in vivo data obtained by Roques et al (2012) for CYP3A and 2B families. Roques et al (2012) demonstrated in rats that fipronil treatment [3.4 mmol/kg/day (equivalent to 1.5 mg/kg/day), per os, for 14 days] increased antipyrine clearance and induced CYP3A1 and CYP2B2 mRNA expressions; although no significant effect on CYP1A1, CYP1A2, and CYP3A2 mRNA expressions was noted. Our work is the first investigation that shows in vivo induction of CYP1A1/2 and 2A1 isoenzymes.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Also our results confirm the in vivo data obtained by Roques et al (2012) for CYP3A and 2B families. Roques et al (2012) demonstrated in rats that fipronil treatment [3.4 mmol/kg/day (equivalent to 1.5 mg/kg/day), per os, for 14 days] increased antipyrine clearance and induced CYP3A1 and CYP2B2 mRNA expressions; although no significant effect on CYP1A1, CYP1A2, and CYP3A2 mRNA expressions was noted. Our work is the first investigation that shows in vivo induction of CYP1A1/2 and 2A1 isoenzymes.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, in rats, oral treatment with fipronil was also associated with high plasma concentration of fipronil sulfone concomitant with a marked increase in the clearance of tyroxine (Leghait et al, 2009). There is a dramatic increase in fipronil biotransformation into fipronil sulfone by hepatic CYP enzymes, and the potential of fipronil sulfone to act as a thyroid disruptor is more critical because it persists much longer in the organism (Roques et al, 2012). Fipronil is readily metabolized into fipronil sulfone in several mammalian species including humans (Mohamed et al, 2004) and this main metabolic pathway is clearly mediated by hepatic phase I CYP enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations